Association Between Hypertensive Disorders of Pregnancy and Later Risk of Cardiomyopathy - Ida Behrens; Saima Basit; Jacob Alexander Lykke; Mattis Flyvholm Ranthe; Jan Wohlfahrt; Henning Bundgaard; Mads Melbye; Heather A. Boyd (2016)
Importance Women with hypertensive disorders of pregnancy, preeclampsia in particular, have an increased risk of cardiomyopathy during the peripartum period. Whether hypertensive disorders of pregnancy are also associated with cardiomyopathy later in life is unknown. Objective To determine whether hypertensive disorders of pregnancy are associated with cardiomyopathy beyond the peripartum period. Design, Setting, and Participants Nationwide register–based cohort study using Cox regression to compare rates of cardiomyopathy in women with and without a history of hypertensive disorders of pregnancy in a cohort of 1 075 763 women with at least 1 pregnancy ending in live birth or stillbirth in Denmark, 1978-2012, with follow-up through December 31, 2012. Exposures A hypertensive disorder of pregnancy (severe or moderate preeclampsia or gestational hypertension) registered in the National Patient Register. Main Outcomes and Measures Cardiomyopathy more than 5 months after delivery (outside the peripartum period) up to 34 years 7 months. Result The women in the primary cohort had 2 067 633 eligible pregnancies during the study period, 76 108 of which were complicated by a hypertensive disorder of pregnancy. During follow-up, 1577 women (mean age, 48.5 years at cardiomyopathy diagnosis; 2.6% with multiple pregnancies) developed cardiomyopathy. Compared with women with normotensive pregnancies (18 211 603 person-years of follow-up; n = 1408 cardiomyopathy events, 7.7/100 000 person-years [95% CI, 7.3-8.2]), women with a history of hypertensive disorders of pregnancy had significantly increased rates of cardiomyopathy (in 173 062 person-years of follow-up among women with severe preeclampsia, n = 27 cardiomyopathy events; 15.6/100 000 person-years [95% CI, 10.7-22.7]; adjusted hazard ratio [HR], 2.20 [95% CI, 1.50-3.23]; in 697 447 person-years of follow-up among women with moderate preeclampsia, n = 102 cardiomyopathy events; 14.6/100 000 person-years [95% CI, 12.0-17.8]; adjusted HR, 1.89 [95% CI, 1.55-2.23]; in 213 197 person-years of follow-up among women with gestational hypertension, n = 40 cardiomyopathy events; 17.3/100 000 person-years [95% CI, 12.7-23.6]; adjusted HR, 2.06 [95% CI, 1.50-2.82]). These increases persisted more than 5 years after the latest pregnancy. Mediation analyses suggested that only about 50% of the association was an indirect association through postpregnancy chronic hypertension. In this cohort, 11% of all cardiomyopathy events occurred in women with a history of hypertensive disorders of pregnancy. Conclusions and Relevance Women with a history of hypertensive disorders of pregnancy, compared with women without such a history, had a small but statistically significant increased risk of cardiomyopathy more than 5 months after delivery. Further research is necessary to understand whether there is a causal mechanism behind this association.